Clear cell sarcoma of the kidney in Austrian children: Long‐term survival after relapse. Issue 5 (12th January 2021) - Friesenbichler, Waltraud; Lüftinger, Roswitha; Kropshofer, Gabriele; Henkel, Martin; Amann, Gabriele; Furtwängler, Rhoikos; Graf, Norbert; Kager, Leo
Abstract: Introduction: Clear cell sarcoma of the kidney (CCSK) is a rare malignant childhood renal tumour. Recently, the central nervous system (CNS) was found to be the most frequent site of relapse associated with a poor outcome. Optimal treatment strategies are scarce. Patients and Methods: Retrospective data analysis of all Austrian children with CCSK. They were enrolled in the Austrian‐Hungarian Wilms Tumour Study (AHWTS) 1989, the SIOP93‐01 or the SIOP2001 study between 1990 and 2019. Demographic, diagnostic, treatment‐related variables and survival data were analysed. Results: We identified 12 children with CCSK (M = 7, F = 5; median age 1.6 years). All had localised disease (stage I: 2; stage II: 2; stage III: 8) at diagnosis, and a first complete remission (CR1) was achieved in 12/12. Six patients are in an ongoing CR1 (median follow‐up 10 years). Six other patients had a relapse (local 1; brain 5) a median time of 2.4 years from diagnosis. Two patients died of the disease 4 months and 2.8 years after first relapse. Four of five patients with CNS relapse are in CR2 with a median follow‐up time of 9.3 years after relapse diagnosis. Relapse treatment included a combination of chemotherapy, radiation and surgery. Two children received high‐dose chemotherapy followed by autologous stem cell rescue, and one child received intrathecal mafosphamide. Long‐term side effects after treatment were impaired tubular renal function (n = 4), cardiomyopathy (n = 1) and growth disorders (n = 1). Conclusions: In this series, the brain was the most common site of relapse. Long‐term survival after recurrence was achievable with intensive multimodal therapy.